HUMAN RESOURCE DEVELOPMENT STRATEGIES IN IMPROVING ORGANIZATIONAL PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Dwi Irawati; Wahyudin; Dinah (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to identify , evaluate , and synthesize empirical evidence regarding human resource development strategies that have been proven effective in improving organizational performance, as well as to analyze the factors that mediate and moderate this relationship based on a systematic literature review approach . The method used is qualitative library research with thematic-inductive content analysis techniques on ten reputable literature sources published between 2021 and 2025 , sourced from the Scopus, Google Scholar, and SINTA databases. The results of the study consistently show that sustainable training and development strategies , digital competency development , structured career management , and transparent and objective performance management systems are the most effective strategies in driving improvements in overall organizational performance . The relationship between HR development strategies and organizational performance is not direct and linear, but is mediated and moderated by a number of crucial factors , including organizational culture , top management commitment , strategic alignment between HRD programs and organizational business objectives , and characteristics of the sectoral context . This study concluded that the effectiveness of HR development strategies requires an integrative , systematic , and adaptive approach , which positions the HR function as a true strategic partner in achieving organizational goals , not just a cost center . This finding has significant implications for public and private sector organizations in developing countries , including Indonesia, in designing sustainable HR development policies oriented towards increasing long -term competitiveness .